Taxonomical position of Annonaceae species from East Java, Indonesia: Collections of Purwodadi Botanic Garden based on morphological character - DEWI AYU LESTARI; RODIYATI AZRIANINGSIH; HENDRIAN HENDRIAN (Biodiversitas Journal of Biological Diversity, 2017)
Lestari DA, Azrianingsih R, Hendrian H. 2017. Taxonomical position of Annonaceae species from East Java, Indonesia: collections of Purwodadi Botanic Garden based on morphological character. Biodiversitas 18: 1067-1076. Morphological characters are one of the most consistent of taxonomical markers are used in Annonaceae today. One of the plants collections from Annonaceae species which came from East Java and conserved in Purwodadi Botanic Garden-Indonesian Institute of Sciences, Purwodadi, and East Java has some problems in morphological characters. It has some problems that causing the taxonomical position of these species are not clear, i.e. presence of unidentified plant until level species. The aim of this study is to classify and identify of species that have not been identified in order to taxonomical position be clearly. Material samples are used Annonaceae collection from East Java and Magnoliaceae as out-group. Samples of these plants were observed qualitatively and quantitatively through morphological characters were analyzed using cluster analysis and then synapomorphy, autapomorphy and apomorphy character analysis to identify and to determine the taxonomical position. The results showed that there are 4 tribes and two sub-families in the dendrogram. Tribe includes Miliuseae, Xylopiae, Annoneae and Uvariae, as well as sub-family of Malmeoideae and Annonoideae. Sub-family distinguished by inner petal and habit, sub-family of Malmeoideae has connate inner petals and trees habit, sub-family of Annonoideae has free inner petal and woody climber habit, some of the trees. Species are unidentified suspected as a different species based on the proximity of group formed. There are five plant species that have not been identified to the species level. These species can be recommended the taxonomical position and proposed of species name through dendrogram with the name of the specimen. Specimen 1 is predicted to have close relations with Annona muricata, specimen 2 is predicted to have close relations with Miliusa macropoda, specimen 3 is predicted to have close relations with Artabotrys uncinatus and identified as Uvaria micrantha, specimen 4 is predicted to have close relations with Fissistigma latifolium and specimen 5 is predicted to have close relations with Saccopetalum horsfieldii, because these species are in one group.